Getting Started: Outfitting the Bride in Seaside - Grant, Gail (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
This paper examines the outfitting of brides-to-be, the period of liminality during which a ‘maid’ is converted to a ‘matron’. Bridal showers are defined as potent women’s rituals which teach the expectations and meanings of the role of wife and the ideal of married domesticity. The form of these rituals is changing; these alterations reflect changing gender arrangements.